Gastronomy and Conquest in the Mexican-American War: Food in the Diary of Susan Magoffin - Berthier-Foglar, Susanne (Diálogos Latinoamericanos, 2005)
The Mexican-American war has never been analyzed from the perspective of gastronomy and eyewitness reports focus on military aspects as well as on the exotic side –and the “colorful” mores– of the invaded population. Since the late 1980s, the New Historians of the West2 have been writing from the viewpoint of those left out by traditional history, nevertheless food is not their focal point. I discuss (colonial and post-colonial) gastronomy and conquest as seen through the eyes of an 18-year old woman, Susan Magoffin following her husband, a 42-year old trader in a caravan along the Santa Fe Trail on the heels of the conquering army. Along the way she kept a diary.3 Not food, but an insider’s view of conquest made her diary a “minor classic”4 worth publishing in 1926 and reprinting in 2000. The Magoffin’s 14 wagon outfit left Independence, Missouri, less than a month after the start of the war –an event that remains largely unmentioned in the diary– and followed the “natural highway for wheeled vehicles across the Great Plains that linked New Mexico to the United States.”5 Gradually other wagon trains joined their party until it reached 75 or 80 wagons (42),6 then 150 (43) explaining why De Voto stated that in New Mexico “Manifest Destiny took the shape of a large-scale freight operation.”7